Options DeMYSTiFieD - McCafferty, Thomas (McGraw-Hill Education, 2010)
Options DeMYSTiFieD reveals why today’s smartest investors rely on the versatility of the options marketplace--and how you can, too! With its quick, snappy explanations and easy-to-understand examples, it provides the knowledge you need to start trading options like a pro in no time. Chapterending quizzes and a final exam round out Options DeMYSTiFieD into a comprehensive self-teaching guide that allows you to learn at your own pace.